Testing the Effect of Smart Egg Puzzle Games on Understanding the Geometry Concepts of Early Childhood - Puspitasari, Endang; Masitoh, Siti; Jannah, Miftakhul (Universitas Malikussaleh, 2019)
This study aims to examine the effects of smart egg puzzle games on understanding the concepts of early childhood geometry. This study uses a type of quasi-experimental research with nonequivalent control group design, where a group of experiments and control groups was not randomly selected. The population in this study were all TK Aisyiyah branches in Ngagel Surabaya, totaling 237 children with a sample of 88 children. Data collection is done by participant observation to determine the understanding of the concept of child geometry. The data analysis technique used is parametric statistics by using one-way ANOVA for samples that correlate with each other. From the results of the analysis obtained Fcount ‰¥ Ftable (21.4 ‰¥ 3.10), this egg puzzle game has a good effect on understanding geometric concepts.